John W. (Jan) Drake: A Biochemical View of a Geneticist Par Excellence. Issue 4 (1st December 2020) - Reha-Krantz, Linda J; Goodman, Myron F
Abstract: John W. Drake died February 2, 2020, a mathematical palindrome, which he would have enjoyed, given his love of "word play and logic, " as stated in his obituary, and echoed by his family..... Abstract: John W. Drake died 02-02-2020, a mathematical palindrome, which he would have enjoyed, given his love of "word play and logic, " as stated in his obituary and echoed by his family, friends, students, and colleagues. Many aspects of Jan's career have been reviewed previously, including his early years as a Caltech graduate student, and when he was editor-in-chief, with the devoted assistance of his wife Pam, of this journal for 15 impactful years. During his editorship, he raised the profile of GENETICS as the flagship journal of the Genetics Society of America and inspired and contributed to the creation of the Perspectives column, coedited by Jim Crow and William Dove. At the same time, Jan was building from scratch the Laboratory of Molecular Genetics on the newly established Research Triangle Park campus of the National Institute of Environmental Health Science, which he headed for 30 years. This commentary offers a unique perspective on Jan's legacy; we showcase Jan's 1969 benchmark discovery of antimutagenic T4 DNA polymerases and the research by three generations (and counting) of scientists whose research stems from that groundbreaking discovery. This is followed by a brief discussion of Jan's passion: his overriding interest in analyzing mutation rates across species. Several anecdotal stories are included to bring alive one of Jan's favorite phrases, "to think like a geneticist." We feature Jan's genetical approach to mutation studies, along with the biochemistry of DNA polymerase function, our area of expertise. But in the end, we acknowledge, as Jan did, that genetics, also known as in vivo biochemistry, prevails.